Nonlinear effects associated with quasi‐electrostatic whistler waves relevant to that in radiation belts. Issue 1 (19th January 2017) - Goyal, R.; Sharma, R. P.; Kumar, S.
Abstract: A model is proposed to study the dynamics of high‐amplitude quasi‐electrostatic whistler waves propagating near resonance cone angle and their interaction with low‐frequency kinetic Alfvén waves (KAWs) in Earth's radiation belts. The wave dynamics clearly indicates the whistlers having quasi‐electrostatic character when propagating close to resonance cone angle. A high‐amplitude whistler wave packet is obtained using the present analysis which has also been observed by S/WAVES (STEREO/WAVES) instrument onboard STEREO (Solar Terrestrial Relations Observatory). A numerical simulation technique has been employed to study the localization of quasi‐electrostatic whistler waves in radiation belts. The ponderomotive force of pump quasi‐electrostatic whistlers (high frequency) is used to excite low‐frequency waves (KAWs). The turbulent spectrum obtained using the analysis suggests the presence of quasi‐electrostatic whistlers and density fluctuations associated with KAW in radiation belts plasma. The wave localization and steeper spectra could be responsible for particle energization or heating in radiation belts. Key Points: Nonlinear interaction of quasi‐electrostatic whistler waves and low‐frequency kinetic Alfven waves High‐amplitude quasi‐electrostatic whistler wave packet Turbulent spectra of waves